Fungsi Agenda Setting Dalam Proses Pembuatan Kebijakan Makassar Ta’ Tidak Rantasa (MTR) Di Kota Makassar - Haris, Umiyati; Irawan, Andri (Jurnal Administrasi Karya Dharma, 2023)
The determination of agenda setting through the MTR (Makassar Tidak Rantasa) policy-making process is inseparable from efforts to create public awareness through waste management issues. This research aims to analyze the agenda setting function in the MTR policy-making process in Makassar City. This type of research is qualitative with a descriptive-analytical method with the aim of analyzing the agenda setting function in the MTR policy-making process in Makassar City. The data collection technique is literature review with data analysis using the Miles and Huberman model data analysis technique. The MTR policy process was analyzed using Fact Analysis and the process of making public policy. The results showed that the agenda setting function in the MTR policy-making process in Makassar City was to shape the mayor's image so that he could be re-elected in the next election. The MTR policy-making process consists of three stages, namely: First, the identification of various needs of the city community, where the most needs are related to environmental cleanliness. Second, the formulation of policy proposals through a decree in the form of instructions by the mayor to SKPD and sub-districts throughout Makassar city. Third, the socialization of MTR policies through jargons such as LISA (See Trash Take); MABELO (Makassar Bersih Lorong); MABASA (Makassar Bebas Sampah) and Aku Dan Sekolahku Tidak Rantasa'. Keywords: Agenda Setting, MTR Policy, Fact Analysis, Process Analysis